Fistulectomy with primary sphincter reconstruction - Seyfried, Steffen; Bussen, Dieter G.; Joos, Andreas; Galata, Christian; Weiß, Christel; Herold, Alexander (International journal of colorectal disease, 2018)
Despite modern medical techniques, anatomically proximal (high) anal fistulas are still a challenge in colorectal surgery. In previous years, the standard of care was complete fistulectomy with a high rate of continence disorders. Over the past 20 to 30 years, sphincter-saving procedures have gained wide acceptance. They represent the technique used in these cases. Additionally, many patients received indefinite treatment, namely the placement of a seton to maintain surgical drainage. The main problem with all fistula surgical possibilities is the high recurrence rate of 30 to 50% in flap procedures and 100% persistence in seton treatments. In recent years, a direct repair (primary reconstruction) in distal fistulas was instigated and shows excellent results. It allowed our technique for proximal (high) anal fistulas to evolve.
Gesehen am 03.12.2020